2018
DOI: 10.18356/6973f578-en
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of factors conditioning the acquisition of academic skills in Latin America in the presence of endogeneity

Abstract: This article identifies the main determinants of skill acquisition in Latin America. Not having repeated a grade, sex, the number of books in the home and the mother's education are defined as individual and family characteristics. In the case of school characteristics, the results are more heterogeneous between countries. The key factors seem to be attending a private school, the number of students per classroom, the quality of the educational materials available, and larger school size and autonomy. The char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition to the role played by the socioeconomic and cultural level of households in explaining the heterogeneity of learning achievements within countries (which is clear in, for example, the positive impact of the mother's level of education, parental expectations and involvement in learning, and the amount of books in the household), research has also shown that inequalities in schools are key to explaining how learning varies between different students in the region (Castro, Giménez and Pérez, 2018;OECD, 2019;UNESCO, 2021a). In their analysis of the factors that affect learning in Latin America, Castro, Giménez and Pérez (2018) conclude that 60% of the variance of students' secondary school results can be explained by the features of schools.…”
Section: Box Ii2mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the role played by the socioeconomic and cultural level of households in explaining the heterogeneity of learning achievements within countries (which is clear in, for example, the positive impact of the mother's level of education, parental expectations and involvement in learning, and the amount of books in the household), research has also shown that inequalities in schools are key to explaining how learning varies between different students in the region (Castro, Giménez and Pérez, 2018;OECD, 2019;UNESCO, 2021a). In their analysis of the factors that affect learning in Latin America, Castro, Giménez and Pérez (2018) conclude that 60% of the variance of students' secondary school results can be explained by the features of schools.…”
Section: Box Ii2mentioning
confidence: 99%
“…Schools that face greater budgetary restrictions, which generally include rural schools, have greater difficulty in attracting teachers with better qualifications and more experience, as well as greater obstacles in their teaching processes owing to the lack or insufficiency of educational materials and physical infrastructure. As regards individual and family-related factors -as well as the negative impact of repeating a year and absence from school, and the positive impact of attendance of a private school and time spent on extra-curricular study-various studies have shown there to be significant gender gaps throughout educational paths and that these are in favour of women in reading and of men in science and mathematics (see chapter III) (Castro, Giménez and Pérez, 2018; UNESCO, 2021a). For OECD, simple averages from the following countries: Australia, Austria, Belgium, Canada, Chile, Colombia, Czechia, Denmark, Estonia, Finland, France, Germany, Grecia, Hungary, Ireland, Iceland, Israel, Italy, Japan, Latvia, Lithuania, Luxemburg, Mexico, Netherlands, Norway, New Zealand, Poland, Portugal, Republic of Korea, Slovakia, Slovenia, Spain, Sweden, Switzerland, Türkiye, the United States of America and the United Kingdom of Great Britain and Northern Ireland.…”
Section: Box Ii2mentioning
confidence: 99%
“…The exclusion of all the missing values in the final sample would have generated a loss of 142,569 observations (39% of our final sample). This would have led to the statistical inference to be biased[53][54][55]. We used data imputation to carry out the analyses, avoiding the reduction of the sample size and mitigating the estimation bias[56].…”
mentioning
confidence: 99%